Effects of Mollugo pentaphylla extract on monosodium urate crystal-induced gouty arthritis in mice - Lee, Yun Mi (BMC Complement Altern Med, 2017)
BACKGROUND: Gout is an inflammatory condition induced by the deposition of monosodium urate (MSU) crystals in joints and soft tissues, and it can lead to acute or chronic arthritis. MSU are pro-inflammatory stimuli that can initiate, amplify and sustain an intense inflammatory response. In this study, we evaluated the anti-inflammatory effect of an extract of Mollugo pentaphylla (MPE) on MSU-induced gouty arthritis in a mouse model. METHOD: An MSU crystal suspension (4 mg/50 μL) was injected intradermally into the right paw. The mice were orally administered MPE (150 mg/kg or 300 mg/kg) or the positive control drug colchicine (1 mg/kg) 1 h before the MSU crystals were injected and then once daily for 3 days. The effects of MPE included inflammatory paw edema and pain upon weight-bearing activity, and we evaluated the inflammatory cytokine expression and paw tissue inflammation-related gene expression. RESULTS: MPE suppressed inflammatory paw edema and pain in the MSU-induced mice. MPE showed anti-inflammatory activity by inhibiting the production of TNF-α, interleukin (IL)-1β, NLRP3 inflammasome and NF-κB. CONCLUSION: These results suggest that MPE has potent anti-inflammatory activities and may be useful as a therapeutic agent against gouty arthritis.